The Influence Of Targets And Without Passing Paired With The Passing Of The Ability Of Young Athletes In Football Academy Persada Sedong Cirebon - Ibnu, Ibnu Adham; Raharjo, Hermawan Pamot; Irawan, Fajar Awang (Journal of Physical Education and Sports, 2024)
This study uses experimental methods, in a pattern that is used is using subjects matched designs, shortened the m-s matching made to subject by subject.Subject of course matching and group meeting, as should the subject of matching is such that the subject of ( pair of subjects ) masing-masing control group experiment and to the group will automatically balance that second group.The methodology experiment can be defined as the methodology used to find the influence of a particular treatment against another in conditions that will. On the ability of pasing football athletes, a partner with the passing target known that the practice of passing partner = 53,50 target has its mean value, 40 minimum =, maximum = 65 and having the standard deviations of 7,626.And that the exercise of passing partner = 64,75 target has its mean value, minimum = 55, maximum = 70 and has the standard deviations of 5,495. On the ability of pasing football athletes, exercise without passing paired with the passing of the ability of young athletes in football academy persada sedong cirebon district with the known that the practice of passing pairs without = 52,25 target has its mean value, 40 minimum =, maximum = 60 and having the standard deviations of 5,955.